Awareness of product-related information, health messages and warnings on alcohol packaging among adolescents: a cross-sectional survey in the United Kingdom. (19th July 2019) - Critchlow, Nathan; Jones, Daniel; Moodie, Crawford; MacKintosh, Anne Marie; Fitzgerald, Niamh; Hooper, Lucie; Thomas, Christopher; Vohra, Jyotsna
Abstract: Background: Alcohol packaging can be used to communicate product-related information, health messages and health warnings to consumers. We examined awareness and recall of such information and messaging among adolescents in the United Kingdom. Method: A cross-sectional survey was conducted with 11–19 year olds in the United Kingdom ( n = 3399), with participants asked if they had seen any information, health messages or warnings on alcohol packaging in the past month (Yes/No) and, if so, what they recalled. We also assessed higher-risk drinking among current drinkers (≥5 Alcohol Use Disorders Identification Test-Consumption) and susceptibility to consume among never-drinkers. Results: One-third (32%) of participants had seen information, health messages or warnings on alcohol packaging. Chi-Square tests showed awareness was greater for current drinkers than non-drinkers (46% vs. 19%; P < 0.001), higher-risk drinkers than lower-risk drinkers (55% vs. 39%; P < 0.001), and susceptible never-drinkers than non-susceptible never-drinkers (21% vs. 16%; P = 0.01). Ten messages were recalled, with drinking responsibly (18%) and not drinking during pregnancy (13%) most recalled. Conclusion: Most young drinkers, including almost half of higher-risk drinkers, did not recall seeing any information, health messages or warnings on alcohol packaging in the past month, suggesting that current labelling is failing to reach this key audience.